2017
DOI: 10.1080/10872981.2017.1379345
|View full text |Cite
|
Sign up to set email alerts
|

Night duty and decreased brain activity of medical residents: a wearable optical topography study

Abstract: Background: Overwork, fatigue, and sleep deprivation due to night duty are likely to be detrimental to the performance of medical residents and can consequently affect patient safety. Objective: The aim of this study was to determine the possibility of deterioration of cerebral function of sleep-deprived, fatigued residents using neuroimaging techniques. Design: Six medical residents were instructed to draw blood from artificial vessels installed on the arm of a normal cooperator. Blood was drawn at a similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
4
12
0
5
Order By: Relevance
“…Cognitive impairments in nurses during the night shift as opposed to the day shift may be mediated predominantly through the decreased alertness and attention that occurs with wake-state instability. This is consistent with previous research, although not focused on nurses [11,12,33].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Cognitive impairments in nurses during the night shift as opposed to the day shift may be mediated predominantly through the decreased alertness and attention that occurs with wake-state instability. This is consistent with previous research, although not focused on nurses [11,12,33].…”
Section: Discussionsupporting
confidence: 94%
“…As far as we know, the present study is the first to attempt to evaluate the disturbances in the brain functions of on-duty nurses by direct assessments of cerebral haemodynamic reactivity measured by PFC oxygenation (decreased rSO 2 ) using a non-invasive NIRS method. Although similar studies have been conducted, they have focused on on-duty medical residents [32,33]. It was found that cerebral perfusion may be an important mechanism, as blood flow, especially to the PFC, directly governs oxygen delivery [34].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study as much as 78% residents reported poor sleep quality on PSQI. Nishida M et al [23] found that the residents' ability to perform relatively simple procedures like withdrawing blood was significantly impaired following night duty, where significant acute sleep deprivation was present, as tested by the ESS and PSQI. Min, A.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is some evidence that several biopsychosocial factors (e.g., circadian rhythms [240][241][242], level of sleepiness [243], and level of arousal [244]) can influence cognitive performance. In particular, it was observed (i) that measures of the cortical hemodynamic response (e.g., obtained during a cognitive test) are associated with total sleep duration [245,246] and sleepiness [247,248] and (ii) that total sleep duration is associated with acute exercise-related changes in behavioral performance (e.g., executive function performance) [82]. Interestingly, the relationship between total sleep duration and acute exercise-related changes in executive function performance are mediated by the volume of the caudate nuclei [82].…”
Section: Resultsmentioning
confidence: 99%